The impacts of service quality dimensions on customer satisfaction of banking sector in Penang, Malaysia - Indrani, Ravinthiran (2021)
Customer satisfaction is a key element for this banking industry which is strongly connected to service quality and it also leads to increased probability when there is improved service quality. Thus, that service quality is the most important factor of success in the banking industry. This study attempts to investigate the impact of service quality dimensions on customer satisfaction in banking sector of Penang, Malaysia. The study aims to determine the impacts of service quality dimensions (Reliability, Responsiveness, Assurance, Empathy, Tangible) on customer satisfaction in banking sector in Penang, Malaysia. The study is conducted to see whether there is any significant relationship between service quality dimensions and customer satisfaction in banking sector, Malaysia. The population of the study are limited to 10 commercial bank branches in Penang. The research sample of this study will be based from the above mentioned 10 commercial bank branches in Penang. Thus, 250 respondents were chosen as the sample size by the researchers. The research instrument used was a questionnaire using a Likert scale and the results were analysed through the Statistical Package for the Social Sciences (SPSS) to measure whether there is a significant relationship between the study variables. In a nutshell, it can be concludes that service quality has a positive influence on customer satisfaction. It explored on the impact of service quality dimensions on customer satisfaction in banking sector and so the findings clearly explain that a good service quality will improve customer satisfaction and vice versa.